Specialized Training of Children and Youngsters in Selected Sports Games - Jaroslav Buchtel; Tomáš Kočíb; Martin Tůma (Karolinum Press, 2014)
Specialized Training of Children and Youngsters in Selected Sports Games The study has two principal goals. The first one is the analysis of personal characteristics of coaches, who function with teams of youth in clubs participating in the top and second to top competitions of adults in handball, tennis and volleyball. Analysis brakes data down following criteria of age, level of education reached and gender. The second goal of our study is the analysis of the sport preparation of children and youth in mentioned sports games on their observation of federations' recommendations about the content of training in respective age groups, including detection of their opinions on the beginning of specialized training for respective playing functions. Research sample was created all-together by 234 coaches (102 volleyball, 69 tennis, 63 handball), who responded to sent non-standard questionnaire with closed and halfopened queries (total rate of return was 67%). Used questionnaire contained eight identifying and five factual questions. Quantitative characteristics were expressed in absolute and relative frequencies, for synoptic presentation of results we have used graphical illustration of responses. Questions concerned players participating in competitions of age groups from about 8 to 19 years. As far as personal composition concerns, the prevailing part of observed sample is created by coaches of age category 30-40 years, out of which about 1/4 are women. We have found significant differences among respective games in the educational sphere. While in tennis and volleyball the university educated coaches creates simple majority (65% and 76% respectively), their portion in handball is only about 40%. The representation of P.E. teachers among respective sports games is similarly different - 83% and 76% respectively in tennis and volleyball, on the contrary to 29% in handball. Tennis possesses very low portion of coaches working with category of youngsters (6%). We have found also differences in opinions regarding to the necessity of preparatory phases, i.e. categories preceding younger pupils. Primarily coaches of tennis assume this phase as inevitable. On the contrary we find the distinctive agreement in opinions concerning early specialization - only a narrow minority of coaches is assured about its benefits (8%). Coaches of tennis and volleyball are in agreement as concerns the start of specialization according to playing functions in older pupils category. The selection of one age category in our group of tennis coaches is impossible. Specializovaný trénink dětí a mládeže ve vybraných sportovních hrách Studie má dva základní cíle. Prvním je analýza osobních charakteristik trenérů působících u družstev mládeže v klubech hrajících první a druhou nejvyšší soutěž dospělých v házené, tenisu a volejbalu. Rozbor je proveden z hlediska kritérií věkových, úrovně edukace a pohlavního složení. Druhým cílem je analýza průběhu sportovní přípravy dětí a mládeže v uvedených sportovních hrách z hlediska respektování svazových doporučení týkajících se obsahu tréninku v jednotlivých věkových kategoriích včetně zjišťování názorů na počátek specializovaného tréninku pro jednotlivé hráčské funkce. Výzkumný soubor tvořilo celkem 234 trenérů (102 volejbal, 69 tenis, 63 házená) kteří odpověděli na zaslaný nestandardizovaný dotazník s polouzavřenými a uzavřenými otázkami (celková návratnost činila 67 %). Použitý dotazník obsahoval osm identifikačních a pět meritorních otázek. Kvantitativní charakteristiky jsou vyjádřeny v absolutních a relativních četnostech, pro přehlednou prezentaci výsledků jsme využili grafického znázornění odpovědí. Otázka se týkaly hráčů a hráček startujících v soutěžích v kategoriích od cca 8 do 19 let. Co se kádrového složení týče, převážnou část sledované skupiny tvoří trenéři věkové kategorie 30-45 let, přičemž žen je asi jedna čtvrtina celého souboru. Výrazné rozdíly mezi jednotlivými hrami jsme nalezli v oblasti edukační. Zatímco v tenisu a volejbalu tvoří vysokoškolsky vzdělaní trenéři nadpoloviční většinu (65, resp. 76 %), v házené je jejich podíl jen cca 40 %. Stejně tak rozdílné je i zastoupení učitelů TV v rámci jednotlivých sportovních her - 83 resp. 76 % v tenisu a volejbalu oproti 29 % v házené. V tenisu je velmi nízké zastoupení trenérů, kteří se věnují dorostenecké kategorii (6 %). Rozdíly jsme nalezli i v názorech na nutnost existence přípravek, tj. kategorií, které předcházejí mladšímu žactvu. Za nezbytnou ji považují především trenéři tenisu. Naopak výraznou shodu nacházíme v názorech na problematiku rané specializace - o její výhodnosti je přesvědčena jen úzká menšina trenérů (8 %). Trenéři volejbalu a tenisu se shodují v začátku specializace dle hráčských funkcí v kategorii staršího žactva, ve skupině tenisových trenérů nelze preferenci jedné věkové kategorie určit.